Firsttrimester Diagnosis and Therapy @ 11–13+6 Weeks of Gestation – Part 2 - von Kaisenberg, Constantin; Kozlowski, Peter; Kagan, Karl-Oliver; Hoopmann, Markus; Heling, Kai-Sven; Chaoui, Rabih; Klaritsch, Philipp; Pertl, Barbara; Burkhardt, Tilo; Tercanli, Sevgi; Frenzel, Jochen; Mundlos, Christine (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
This extensive AWMF 085-002 S2e-guideline “First Trimester Diagnosis and Therapy @ 11–13+6 Weeks of Gestation” has systematically analyzed high-quality studies and publications and the existing evidence (evidence tables) and produced recommendations (level of recommendation, level of evidence, strength of consensus).This guideline deals with the following topics in the context of the 11–13+6 weeks scan: the legal basis, screening for anatomical malformations, screening for chromosomal defects, quality assessment and audit, screening for preeclampsia and FGR, screening for preterm birth, screening for abnormally invasive placenta (AIP) and placenta accreta spectrum (PAS), screening for velamentous cord insertion and vasa praevia, screening for diabetes mellitus and LGA.Screening for complications of pregnancy can best be carried out @ 11–13+6 weeks of gestation. The issues of how to identify malformations, chromosomal abnormalities and certain disorders of placentation (high blood pressure and proteinuria, intrauterine growth retardation) have been solved. The problem of how to identify placenta percreta and vasa previa has been partially solved. What is still unsolved is how to identify disorders of glucose metabolism and preterm birth.In the first trimester, solutions to some of these problems are available: parents can be given extensive counselling and the risk that a pregnancy complication will manifest at a later stage can be delayed and reduced. This means that screening is critically important as it helps in decision-making about the best way to manage pregnancy complications (prevention and intervals between follow-up examinations).If no treatment is available and if a termination of pregnancy is considered, the intervention can be carried out with far lower complications compared to the second trimester of pregnancy. In most cases, further examinations are not required and the parents can be reassured. A repeat examination at around week 20 of gestation to complete the screening for malformations is recommended.Note The guideline will be published simultaneously in the official journals of both professional societies (i.e. Ultraschall in der Medizin/European Journal of Ultrasound for the DEGUM and Geburtshilfe und Frauenheilkunde for the DGGG).In dieser umfassenden AWMF 085-002 S2e-Leitlinie „Ersttrimester Diagnostik und Therapie @ 11–13+6 Schwangerschaftswochen“ werden die qualitativ hochwertigen Studien und Publikationen bzw. die vorliegende Evidenz (Evidence Tables) systematisch analysiert und Empfehlungen formuliert (Empfehlungsgrad, Evidenzgrad, Konsensstärke). Die LL behandelt zum Zeitpunkt 11–13+6 Schwangerschaftswochen folgende Themen: rechtliche Grundlagen, Screening für Fehlbildungen, Screening für Chromosomenstörungen, Qualitätssicherung und Audit, Screening für Präeklampsie und FGR, Screening für Frühgeburt, Screening für Abnormal Invasive Placenta (AIP) und Placenta Accreta Spectrum (PAS), Screening für Insertio velamentosa und Vasa praevia, Screening für Diabetes mellitus und LGA. Der Zeitpunkt 11–13+6 Schwangerschaftswochen ermöglicht die Suche nach Schwangerschaftsproblemen. Gelöst ist die Suche nach Fehlbildungen, Chromosomenstörungen und Plazentaproblemen (hoher Blutdruck und Eiweißausscheidung, intrauterine Wachstumsretardierung). ZumTeil gelöst ist die Suche nach Placenta percreta und Vasa praevia. Ungelöst ist die Suche nach Glukosestoffwechselstörungen und Frühgeburt.Für einen Teil der Probleme existieren im ersten Trimenon Lösungsansätze, die Eltern können intensiv beraten werden; die Wahrscheinlichkeit, dass sich ein Schwangerschaftsproblem später manifestiert, kann hinausgezögert und gesenkt werden. Dies macht die Untersuchung für die Entscheidungsfindung bezüglich des besten Managements (Intervalle der Follow-up-Untersuchungen und Prävention) unverzichtbar. Besteht keine Therapie bzw. wird ein Schwangerschaftsabbruch erwogen, kann dieser mit viel niedrigeren Komplikationsraten als im zweiten Trimenon angeboten werden. In den meisten Fällen sind weiterführende Untersuchungen nicht erforderlich und die Eltern können beruhigt werden. Eine erneute Untersuchung um 20 Schwangerschaftswochen zur Vervollständigung der Fehlbildungsdiagnostik wird empfohlen.Hinweis Die Leitlinie wird gleichzeitig in den offiziellen Zeitschriften beider Fachgesellschaften (d.h. Ultraschall in der Medizin/European Journal of Ultrasound für die DEGUM und Geburtshilfe und Frauenheilkunde für die DGGG) veröffentlicht.
Keywords: first-trimester screening; nuchal translucency; chromosomal disorders; malformations; preeclampsia